2009
DOI: 10.1073/pnas.0902510106
|View full text |Cite
|
Sign up to set email alerts
|

PDGF-A interactions with fibronectin reveal a critical role for heparan sulfate in directed cell migration during Xenopus gastrulation

Abstract: Platelet-derived growth factor (PDGF) signaling is essential for processes involving cell motility and differentiation during embryonic development in a wide variety of organisms including the mouse, frog, zebrafish, and sea urchin. In early Xenopus laevis embryos, PDGF-AA provides guidance cues for the migration of anterior mesendoderm cells as they move across a fibronectin-rich extracellular matrix. The long form of PDGF-A includes a positively charged carboxyl-terminal retention motif that can interact wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
55
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 58 publications
6
55
0
Order By: Relevance
“…Indeed, VEGF-A, a factor known to bind heparin/HSPGs in a SULF-dependent manner (18,78,79), can directly activate PDGFRα (80). Furthermore, we observed a slight but consistent decrease in the total levels of PDGFRα.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Indeed, VEGF-A, a factor known to bind heparin/HSPGs in a SULF-dependent manner (18,78,79), can directly activate PDGFRα (80). Furthermore, we observed a slight but consistent decrease in the total levels of PDGFRα.…”
Section: Discussionsupporting
confidence: 50%
“…Furthermore, Sulf2 expression is increased in many PDGFB-driven tumors regardless of the insertion site (77). Finally, PDGFs interact with HSPGs, and this interaction is influenced by 6-O-sulfation (18,78,79).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the presence of a heparin-binding domain within the GFs seems to be necessary, but not sufficient, to provide binding to Fg β15-66 (2) . We and others have shown enhanced binding of GFs to fibronectin in the presence of heparin, although heparin is not the linker between the two molecules (3,4,27). It has been suggested that heparin and heparan sulfate can change the conformation of fibronectin and increase its affinity for GFs (4,27); however, in the case of GF-Fg β15-66 (2) interaction, heparin did not increase GFbinding ability, but rather decreased it (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…For example, many GFs are able to bind the proteoglycan components of the ECM (2). Moreover, it has recently become more evident that ECM proteins such as fibronectin and vitronectin, which do not contain highly negatively charged sugar chains, bind several GFs (3)(4)(5)(6)(7)(8). In addition to sequestration of GF by ECM components, the ECM also can modulate cosignaling between adhesion and GF receptor systems.…”
mentioning
confidence: 99%